A hollow Co3−xCuxS4 with glutathione depleting and photothermal properties for synergistic dual-enhanced chemodynamic/photothermal cancer therapy. Issue 39 (21st September 2022) - Jiang, Ying; Lu, Hao; Yuan, Xiangyang; Zhang, Yuanyuan; Lei, Lingli; Li, Yongcan; Sun, Wei; Liu, Jing; Scherman, Daniel; Liu, Yingshuai
Abstract : We have developed a hollow bimetallic sulfide Co3− x Cu x S4 by doping copper ions (Cu 2+ ) into ZIF-67-derived Co3 S4 for synergistic dual-enhanced chemodynamic/photothermal cancer therapy. Abstract : Chemodynamic therapy has become an emerging cancer treatment strategy, in which tumor cells are killed through toxic reactive oxygen species (ROS), especially hydroxyl radicals (˙OH) produced by the Fenton reaction. Nevertheless, low ROS generation efficiency and ROS depletion by cellular antioxidant systems are still the main obstacles in chemodynamic therapy. In the present work, we propose a dually enhanced chemodynamic therapy obtained by inhibiting ˙OH consumption and promoting ˙OH production based on the administration of bimetallic sulfide Co3− x Cu x S4 nanoparticles functionalized by polyethylene glycol. These bimetallic nanoparticles display glutathione depleting and photothermal properties. The nanoparticles are gradually degraded in a tumor microenvironment, resulting in Co 2+ and Cu 2+ release. The released Co 2+ triggers a Fenton-like reaction that turns endogenous hydrogen peroxide into highly toxic ˙OH. In the cellular environment, Cu 2+ ions are reduced to Cu + by endogenous GSH, which decreases the intracellular antioxidant capacity and additionally up-regulates ˙OH production via the Cu + -induced Fenton-like reaction. Moreover, under near-infrared light irradiation, the bimetallic nanoparticles display a photothermal conversion efficacy of 46.7%, which not only improves chemodynamic therapy via boosting a Fenton-like reaction but results in photothermal therapy through hyperthermia. Both in vitro cancer cell killing and in vivo tumor ablation experiments show that the bimetallic nanoparticles display outstanding therapeutic efficacy and negligible systemic toxicity, indicating their anticancer potential.